Homesick or Sick of Home? - Laura Luise Schultz (Kvinder, Køn & Forskning)
Review of Anna Meera Gaonkar: Feeling Sick of Home? A Cultural Study of Postmigrant Homesickness in Contemporary Denmark University of Copenhagen 2022, PhD Dissertation.